2016
DOI: 10.1016/j.bbagen.2015.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Syk negatively regulates TLR4-mediated IFNβ and IL-10 production and promotes inflammatory responses in dendritic cells

Abstract: Background While Syk has been shown to associate with TLR4, the immune consequences of Syk-TLR interactions and related molecular mechanisms are unclear. Methods Gain- and loss- of function approaches were utilized to determine the regulatory function of Syk and elucidate the related molecular mechanisms in TLR4-mediated inflammatory responses. Cytokine production was measured by ELISA and phosphorylation of signaling molecules determined by western blotting. Results Syk deficiency in murine dendritic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 60 publications
(77 reference statements)
0
19
0
1
Order By: Relevance
“…SH2 domains selectively bind to the phosphorylated immunoreceptor tyrosine-based activation motifs (ITAMs) of immune receptors, such as MyD88, TRAF6, and TRIF, transmitting initiative signals to downstream pathways. SYK is found to be fundamental for Toll-like receptor signaling pathway and the inhibition of SYK suppresses the release of proinflammatory cytokines [ 25 , 26 ]. In this study, we detected alterations of SYK in protein level but not mRNA level.…”
Section: Discussionmentioning
confidence: 99%
“…SH2 domains selectively bind to the phosphorylated immunoreceptor tyrosine-based activation motifs (ITAMs) of immune receptors, such as MyD88, TRAF6, and TRIF, transmitting initiative signals to downstream pathways. SYK is found to be fundamental for Toll-like receptor signaling pathway and the inhibition of SYK suppresses the release of proinflammatory cytokines [ 25 , 26 ]. In this study, we detected alterations of SYK in protein level but not mRNA level.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, L. major alters macrophage (BALB/c-derived peritoneal macrophages) CD40 signalosome composition by depleting cholesterol, resulting in the induction of IL-10 production rather than IL-12 [136]. This alteration is regulated by TNF receptor associated factor 6 (TRAF6) and spleen tyrosine kinase (SYK) which both have been shown to regulate mTORC1 signaling, suggesting that mTORC1 signaling is involved in the altered CD40 signalosome composition by L. major [137,138]. Interestingly, cholesterol activates mTORC1 at the lysosomal surface, which indicates that alterations in cholesterol levels elicited by pathogens could, in addition to membrane composition, alter mTORC1 activation [139].…”
Section: Membranesmentioning
confidence: 99%
“…Syk involvement in the regulation of signals generated by the engagement of TLR-4 complex by its ligand LPS in human neutrophils and macrophages has also been previously demonstrated (Arndt et al 2004;Ulanova et al 2007;Miller et al 2012), and this mechanism likely operates in our model. Recent studies expanded our understanding of the role of Syk in fine-tuning of cellular responses stimulated by the engagement of innate immune receptors (Aouar et al 2016;Yin et al 2016). For example, it was D r a f t demonstrated that in macrophages and dendritic cells, Syk regulates TNFα exocytosis induced by stimulation of TLR9 by bacterial CpG DNA (Rao et al 2013); such mechanism may potentially be involved in responses of differentiated THP-1 cells to P. aeruginosa.…”
Section: R a F Tmentioning
confidence: 99%